The effects of automation on the staffing patterns of the University of the Philippines Diliman Main Library - Taduran, Richard Jonathan O. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
The automation of the University of the Philippines Main Library was implemented in 1985, with Mary Jane Ruhl's feasibility report as its strategic core. The program was one of the main highlights of the U.P. Diliman Development Plan (1985-1989).Because of this, the Computer Services Division and the Information Technology Officer position were created, affecting the library's organizational structure in 1987. Changes in the staffing pattern took place in the next few years, but hey were mainly due to personnel matters. Though automation held no other effect on the Main Library's Staffing, the staff themselves were greatly affected by the program, since most of them work with computers every day. Automation made a great deal of impact as most of them adapted their professional lives to computer training.